Lideranças estatais, uma história da integração regional: Brasil e Venezuela 2003-2010 - Silva, Robson Santiago da (2021)
This research intends to comprehend the foreign policy’s political agenda from Brazil and Venezuela, related to the regional integration and to their respective proposals of international insertion during the period between 2003 and 2010, that covers the two presidential terms of Luiz Inácio Lula da Silva (2003-2010), and large part of Hugo Rafael Chávez Frias’ (1999-2012) presidential terms. The rising of the two presidents in South America, as long as other region’s leaders in this period, would be seen by the social analysts as a new wave of presidents connected to the left of the political spectrum. Therefore, it was an answer to the effects of the neoliberal process during the nineties. Given that background, there’s a hypothesis that Brazil and Venezuela have resized the state actions and they were decisive to think of building a process based on a new perspective that would consider internal social aspects and the discrepancies between the nations, and not considering the traditional trading elements to the regional integration only.The methodology for such study was based on the analysis of historical documents, consisting of 15 speeches by President Lula and 6 by President Chávez, given at the summit meetings of Heads of State of Mercosur during the highlighted period, as documentation for the research on the topic of regional integration. Furthermore, the opening speeches of both presidents composed the documental corpus. This research, then, intends to analyse the moments when has been discussed the regional integration in the subcontinent, restoring this historical issue from CEPAL’s observations, created in 1949, until the 1990’s experiences; and next, it analyses the foreign policies’ inflection of Lula and Chavez. The actions of these leaderships were fundamental to rehearse a process of integration with a new foreign policy agenda and international insertion based on cooperation and reassurance of the idea of sovereignty to the Latin-American nations